Evaluation of the Rutting Performance of Hot-Mix Asphalt Concrete Containing Ferrochrome Slag Aggregate - Hossam F. Hassan; Khalid Al-Shamsi; Khalifa Al-Jabri; Saba Al Amri (Construction Materials)
Ferrochrome (FeCr) slag is a by-product of high-carbon ferrochromium, which is used in the manufacturing of stainless steel. In this study, FeCr was evaluated as a replacement for natural aggregates in hot-mix asphalt (HMA) bituminous base and wearing course layers. Four mixes were designed according to the Superpave mix design procedure, one control and three mixes, with FeCr slag replacing coarse, fine, or total aggregate. FeCr slag exhibited higher angularity and surface roughness than natural aggregates, resulting in an increased number of voids in mineral aggregate (VMA) and increased binder content. Performance testing using dynamic modulus, finite element analysis, and rutting evaluation using the MEPDG rut model showed that rutting increased with increased slag content. However, mixes with coarse aggregate replacement performed better than those with fine aggregate replacement. TCLP testing indicated that the FeCr slag is environmentally safe. The heavy metal leachate content was well below regulatory limits. Economic analysis showed material cost savings of up to 44% and 4% in the bituminous base and wearing course layers, respectively. The findings support the use of FeCr slag as a coarse aggregate replacement in asphalt mixes, offering both environmental and economic benefits.